Range Extension of an Exotic Terrestrial Snail, Deroceras laeve (O. F. Müller, 1774) and Recent Exotic Mollusca of Arunachal Pradesh, North East India - Gurumayum, Shantabala Devi (Indian Forester, 2024)
Present study reports the occurrence of an exotic terrestrial snail, Deroceras laeve (O. F. Müller, 1774) for the first time from the state of Arunachal Pradesh. A total of 7 exotic mollusca species found inhabiting both land and freshwater systems of the state that belongs to 3 orders, 7 families and 7 genera under the class gastropoda are documented. All the reported species have been found to be invasive in one way or other and some of them namely Physa acuta, Deroceras leave, Bradybaena similaris, and Lissachatina fulica are included in Invasive Species Compendium of CABI (Centre for Agriculture and Bioscience International) list. The ubiquitous presence of Lissachatina fulica which is included in the 100 most invasive species of the Global Invasive Species Database of IUCN in many parts of the state, is a cause for concern specially for environmental ecologist as the state is included in 36 recognized Biodiversity hot spot region of the word.